Using Qualitative System Dynamics Analysis to Promote Inclusive Livestock Value Chains: A Case Study of the South African Broiler Value Chain - Cuevas Garcia-Dorado, Soledad; Queenan, Kevin; Shankar, Bhavani; Häsler, Barbara; Mabhaudhi, Tafadzwanashe; Cooper, Gregory; Slotow, Rob (Frontiers in Sustainable Food Systems, 2021)
Livestock value chains globally are increasingly dualistic, with integrated market-leaders co-existing with comparatively disadvantaged small producers who, nevertheless, support rural livelihoods and food access, and can also contribute to more resilient supply chains. The South African broiler value chain provides a highly illustrative case study. The purpose of this study is to identify potential leverage points for policy intervention to support small and emerging producers in the South African broiler value chain, and to discuss the strengths and limitations of system dynamics approaches to promote inclusive food value chains. This study develops a causal loop diagram (CLD) based on semi-structured stakeholder interviews and policy documents. The main challenges, key variables and causal relationships between them are systematically identified. Variables are coded, generalised and graphically represented, and entry points for intervention and their links to existing policies are mapped. The challenges faced by smallholders in the context of our study can be characterised, using a CLD, as a set of interlinked and reinforcing dynamics which perpetuate existing disadvantages and reinforce duality in the value chain. Key policy entry points have been identified that could be targeted by a coordinated policy package, including: Direct support for infrastructure investment and input access through grants, subsidies or other policies; credit and liquidity provision for day-to-day expenses; creation of aggregation mechanisms for both inputs and outputs; regulations or initiatives that directly target the relationship of farmers with the commercial segment to improve access to day-old-chicks and, finally, training in business and technical skills. Although most of these interventions have been addressed at some point, implementation has been fragmented, failing to fully consider their complementary nature, thus undermining effectiveness. Existing approaches to consensus building and stakeholder participation in system dynamics research can present challenges when it comes to engaging with complex policy processes and issues of conflict of interest that are relevant in the context of smallholder promotion and equitable food systems, Despite these methodological challenges we find that there is considerable scope for system dynamics approaches to inform policy for smallholder promotion, even in contexts characterised by complex policy processes.